Implementation of Saintific Approach Based on STEM Education to Increase Scientific Literacy - Wijayanti, Arfilia; Fajriyah, Khusnul; Priyanto, Wawan (Unnes Science Education Journal, 2020)
This study aims to determine the effectiveness of the saintific approach based on STEM education to improve scientific literacy. This research was conducted with an experimental method in which the sample consisted of one experimental class that received a treatment, namely given learning with a scientific approach based on STEM (Science, Technology, Engineering, and Mathematics) education and one control class given learning with a scientific approach, then in the end of learning is analyzed its effectiveness by calculating the magnitude of the increase (N-Gain) of scientific literacy, as well as the responses of prospective teacher students at Universitas PGRI Semarang to the learning process that has been carried out. It was concluded that the saintific approach based on STEM education was effective in increasing the scientific literacy of elementary school teacher candidates. The average value of N-gain for the the experimental class was obtained 0.61 in the high category and the control class was 0.34 in the medium category. The learning processes applied saintific approach based on STEM education get very good response, especially in an effort to improve scientific literacy of elementary school teacher candidates.